2021
DOI: 10.1371/journal.pone.0253798
|View full text |Cite|
|
Sign up to set email alerts
|

The interactive effect of pH variation and cadmium stress on wheat (Triticum aestivum L.) growth, physiological and biochemical parameters

Abstract: Anthropogenic activities such as mining, manufacturing, and application of fertilizers release substantial quantities of cadmium (Cd) into the environment. In the natural environment, varying pH may play an important role in the absorption and accumulation of Cd in plants, which can cause toxicity and increase the risk to humans. We conducted a hydroponic experiment to examine the impact of pH on cadmium (Cd) solubility and bioavailability in winter wheat (Triticum aestivum L.) under controlled environmental c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 74 publications
3
8
0
Order By: Relevance
“…An LCA-4 ADC portable infrared gas analyzer (Analytical Development Company, Hoddesdon, England) was used to measure the gas exchange parameters. Each plant's second upper fully expanded leaf was selected to measure photosynthetic parameters such as photosynthetic rate, stomatal conductance, sub-stomatal conductance, and transpiration rate measured according to the procedures described earlier in [9,94]. To ensure unchanged photon flux density and temperature, readings were made at a similar time each day (between 10:00 a.m. and 12:00 p.m.) by clamping the central part of the leaf in the chamber of the instrument.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An LCA-4 ADC portable infrared gas analyzer (Analytical Development Company, Hoddesdon, England) was used to measure the gas exchange parameters. Each plant's second upper fully expanded leaf was selected to measure photosynthetic parameters such as photosynthetic rate, stomatal conductance, sub-stomatal conductance, and transpiration rate measured according to the procedures described earlier in [9,94]. To ensure unchanged photon flux density and temperature, readings were made at a similar time each day (between 10:00 a.m. and 12:00 p.m.) by clamping the central part of the leaf in the chamber of the instrument.…”
Section: Methodsmentioning
confidence: 99%
“…In the end, the absorption of supernatant was calculated at three different wavelengths, namely 450, 532 and 600, to estimate leaf MDA contents by using the following equation. The details of the determination of the biochemical parameters are given in [94,95].…”
Section: Methodsmentioning
confidence: 99%
“…Biochar has the ability to immobilize organic contaminants [53] and HMs [54] through different mechanisms, such as physical adsorption [38]; chemical adsorption with Ca 2+ , Mg 2+ , K + , Na + , and S [16,37,38]; complexation with Pb 2+ and Cu 2+ [4,37]; the formation of precipitates through phosphate compounds [4,55,56]; and precipitation as a result of pH elevation [13,57]. So far, the extent to which one or more of these different mechanics contributes to HM immobilization by different feedstock is still unknown, although many researchers have reported that it is mostly affected by soil reaction (pH) [41,58].…”
Section: Heavy Metal Immobilization Mechanismsmentioning
confidence: 99%
“…Several factors (feedstock particle size and type, as well as pyrolysis temperature) affect biochar characteristics and functions. The wide range of biochar properties enables it to be the most suitable material for dealing with and remediating various HM-contaminated soils [13]. The key properties of biochar are affected by pre-treatments resulting in enhancing biochar's ability to immobilize HMs [14].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their toxic nature, the regular release of these elements produces risk to both environment and human health through the food chain and other human exposure pathways [1][2][3]. One of the crucial sources of soil contamination are anthropogenic activities such as combustion of fossil fuels, smelting, and the use or production of metallic compounds, which are accountable for most of the trace element contamination [4,5]. Crowded traffic roads may emit massive pollutants such as heavy metals into the environment (soil, air, and water) and can pose severe threats to human health because of their persistency and bioaccumulation in the terrestrial environment [6][7][8].…”
Section: Introductionmentioning
confidence: 99%